Transient flow, flow pattern characterisation and performance evaluation of a two-phase natural circulation heat transfer loop - Senda, Paul Tudieji (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.